ANALISIS SISTEM PENGENDALIAN INTERNAL ATAS SIKLUS PENGGAJIAN PADA CV CAHYO UTOMO KUBAH - Devika Putri Lestari; Erna Puspita; Hestin Sri Widiawati (ADISAM PUBLISHER, 2023)
This study uses a qualitative method with a case study approach. This research was conducted at CV Cahyo Utomo Kubah which is located in Sumbersari Hamlet, Mojokendil Village, Ngronggot District, Nganjuk Regency. The data used are Primary Data and Secondary Data. Data collection is done by Interview, Observation, and Documentation. To obtain the validity of the data findings, this study used a technique of checking the validity of the triangulation data, namely the data source triangulation technique and the method triangulation technique. The informants of this study are the owner and director of CV Cahyo Utomo Dome, the finance department and production employees. The analysis technique used is as follows, namely by explaining the internal control system in the payroll cycle of CV Cahyo Utomo Kubah., Explaining the existing payroll procedures of CV Cahyo Utomo Kubah and comparing the payroll accounting information system in the company with the theory of the accounting system according to Mulyadi. The results of the research show that at CV Cahyo Utomo the division of tasks has not been carried out properly, because there are still dual tasks carried out by the finance department, namely making payroll and paying salaries which should be separated, there are no documents in the form of salary slips that should be received by employees at when receiving a salary, this is clearly detrimental to employees.